From "Eternal Heaven" to "Nomadic Rationality": An Ecophilosophical Interpretation of Traditional Mongolian Ecological Thought - Wang, Quan; Purevsuren, B. (Education Insights, 2026)
"Eternal Heaven" is a foundational concept in traditional Mongolian thought and a key entry point for understanding the cosmic order, the order of life, and the order of conduct in nomadic society. Existing studies have primarily approached this concept from the perspectives of religious belief, ethnic culture, and ecological wisdom, yet they have not fully explained how "Eternal Heaven" can be brought into the broader ecophilosophical discussion of "ecological rationality." Drawing on foundational texts such as The Secret History of the Mongols, comprehensive studies of Tengri belief, extensive scholarship on the Mongolian ecological outlook, and key theoretical writings in contemporary ecological philosophy, this article argues that "Eternal Heaven" is not merely an object of religious worship. Rather, it functions as a sophisticated conceptual structure generated within the unique historical experience of steppe nomadism. It takes profound reverence for Heaven and Earth as its fundamental spiritual premise, continuous adaptation to natural environmental rhythms as its primary cognitive mode, and moderate resource use together with dynamic ecological balance as its guiding principles of conduct. On this theoretical basis, the article proposes the novel concept of "nomadic rationality" in order to systematically summarize the distinct form of rationality embedded in traditional Mongolian ecological thought. This unique form of rationality effectively unites deep cosmological grounding, pragmatic everyday wisdom, and strong normative force, offering valuable insights for modern environmental ethics and sustainable development paradigms.